2022
DOI: 10.3389/fimmu.2022.1004023
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced networks and disturbed kinetics of serum soluble mediators associated with distinct disease outcomes in severe COVID-19 patients

Abstract: The present study applied distinct models of descriptive analysis to explore the integrative networks and the kinetic timeline of serum soluble mediators to select a set of systemic biomarkers applicable for the clinical management of COVID-19 patients. For this purpose, a total of 246 participants (82 COVID-19 and 164 healthy controls – HC) were enrolled in a prospective observational study. Serum soluble mediators were quantified by high-throughput microbeads array on hospital admission (D0) and at consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, in our cohort, we found decreased PDGFb, especially in mild patients compared to controls. This is consistent with a previous study that found decreased serum PDGFb levels in COVID-19 patients compared to controls [49]. A recent study found that lower levels of PDGFb in the serum of COVID-19 patients compared to healthy controls within the first 24 h of hospitalization predict mortality [50].…”
Section: Discussionsupporting
confidence: 92%
“…However, in our cohort, we found decreased PDGFb, especially in mild patients compared to controls. This is consistent with a previous study that found decreased serum PDGFb levels in COVID-19 patients compared to controls [49]. A recent study found that lower levels of PDGFb in the serum of COVID-19 patients compared to healthy controls within the first 24 h of hospitalization predict mortality [50].…”
Section: Discussionsupporting
confidence: 92%
“…In a mouse model of COVID-19 infection, HA production in the lung could be triggered by IL-13 administration and reduced by blockade of IL-13 in conjunction with less HAS1 expression, suggesting that this cytokine could contribute to HA levels in COVID-19. Consistent with this, IL-13 was increased in serum samples from a cohort of 178 COVID-19 patients [159] and in a second study of 138 COVID-19 patients [160] . However, in another study of 82 patients with severe COVID-19, IL-13 was decreased [159] .…”
Section: Ha Is Abundant In Acute Covid-19 Ardsmentioning
confidence: 53%
“…Consistent with this, IL-13 was increased in serum samples from a cohort of 178 COVID-19 patients [159] and in a second study of 138 COVID-19 patients [160] . However, in another study of 82 patients with severe COVID-19, IL-13 was decreased [159] . IL-13 was also not increased in a small study of human respiratory secretions from 22 patients [137] .…”
Section: Ha Is Abundant In Acute Covid-19 Ardsmentioning
confidence: 53%